Impact of Effectiveness and Efficiency of Internal Audit on Improving Financial Performance: A Field Study in Banks Operating in Yemen - Dr. Sultan Ali Ahmed Al-Sorihi; Hamid Sa'ad Mohsen Al-Salafi (مجلة الدراسات الاجتماعية, 2019)
This study aimed to examine the impact of the efficiency and effectiveness of internal audit in improving financial performance on banks operating in Yemen. To achieve this objective, a questionnaire was used to collect data from the population, where 216 questionnaires were distributed to a sample of board members, audit committees, internal audit and financial management of banks. After colecting the data, the statistical multiple regression analysis was used to test the hypotheses of the study. The study findings revealed a high positive impact of the effectiveness and efficiency of internal audit on improving financial performance in banks. The findings also showed that the impact of effectiveness of internal audit was higher than that of its efficiency. Based on these results, it was recommended to pay attention to the effectiveness of internal audit, including its dimensions: (purpose, authority and responsibility) and (independence and objectivity). Attention should also be paid to the efficiency of internal auditing, including its dimensions: (professional diligince and skills) and (quality improvement program). It was also recommended to implement the recommendations of the bank internal auditors who should be independent and directly affiliated to the senior management and the audit committee.